Progressive Muscle Relaxation Therapy to Lower High Blood Pressure in the Elderly Through Community Service Midwifery Lecturer Unand - Uliy Iffah; Novi Aulia Driza; Nurul Aminah; Dina Taufia; Henni Fitria (Jurnal sosial dan sains, 2024)
Background: Elderly health is an increasingly urgent aspect in today's social dynamics. With the increasing number of elderly people in the population, healthcare challenges specific to them are increasingly important to discover. Purpose: This study aims to analyze Progressive Muscle Relaxation Therapy to Lower High Blood Pressure in the Elderly Through Community Service Method: A series of activities were carried out in several stages, with active participation from the elderly Results: The results are in line with previous research that has also shown the effectiveness of this therapy in lowering blood pressure and relieving stress in the elderly population. Increased understanding of progressive muscle relaxation therapy is an important first step in the management of high blood pressure. Participants who better understand these relaxation techniques can use them as aids to maintain their health in the long term. Conclusion: Community service by applying progressive muscle relaxation therapy has proven its benefits in lowering high blood pressure in the elderly. Increased understanding of this therapy, decreased blood pressure, and increased feelings of relaxation are encouraging results